Three-Dimensional Cell Culture Methods in Infectious Diseases and Vaccine Research - Gamze Varan; Serhat Unal (MDPI AG, 2023)
Cells, the basic structures of all living organisms, reside in an extracellular matrix consisting of a complex three-dimensional architecture and interact with neighboring cells both mechanically and biochemically. Cell-cell and cell-extracellular matrix interactions form a three-dimensional network that maintains tissue specificity and homeostasis. Important biological processes in a cell cycle are regulated by principles organized by the microenvironment surrounding the cell. The conventional cell culture methods failed to mimic in vivo-like structural organization and are insufficient to examine features such as connectivity of cells, cellular morphology, viability, proliferation, differentiation, gene and protein expression, response to stimuli, and drug/vaccine metabolism. Three-dimensional cell culture studies are very important in terms of reducing the need for in vivo studies and creating an intermediate step. Three-dimensional cell culture methods have attracted attention in the literature in recent years, especially in examining the cellular distribution of organs in the presence of infectious diseases, elucidating the pathogenic mechanism of action of viruses, and examining virus-host interactions. This review highlights the use and importance of three-dimensional cell culture methods in the design and characterization of novel vaccine formulations and the pathogenesis of infectious diseases.